End-group-functionalized poly(N,N-diethylacrylamide) via free-radical chain transfer polymerization: Influence of sulfur oxidation and cyclodextrin on self-organization and cloud points in water - Reinelt, Sebastian; Steinke, Daniel; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2014)
In this work we report the synthesis of thermo-, oxidation- and cyclodextrin- (CD) responsive end-group-functionalized polymers, based on N,N-diethylacrylamide (DEAAm). In a classical free-radical chain transfer polymerization, using thiol-functionalized 4-alkylphenols, namely 3-(4-(1,1-dimethylethan-1-yl)phenoxy)propane-1-thiol and 3-(4-(2,4,4-trimethylpentan-2-yl)phenoxy)propane-1-thiol, poly(N,N-diethylacrylamide) (PDEAAm) with well-defined hydrophobic end-groups is obtained. These end-group-functionalized polymers show different cloud point values, depending on the degree of polymerization and the presence of randomly methylated β-cyclodextrin (RAMEB-CD). Additionally, the influence of the oxidation of the incorporated thioether linkages on the cloud point is investigated. The resulting hydrophilic sulfoxides show higher cloud point values for the lower critical solution temperature (LCST). A high degree of functionalization is supported by 1H NMR-, SEC-, FTIR- and MALDI–TOF measurements.
Keywords: chain-transfer polymerization; cyclodextrins; end-group functionalization; host–guest interaction; lower critical solution temperature (LCST); poly(N,N-diethylacrylamide)

(untitled) - Lehn, J. M. (Pure Appl. Chem., 1978)

(untitled) - Lehn, J.-M. (Angew. Chem., Int. Ed. Engl., 1990)

(untitled) - Fischer, E. (Ber. Dtsch. Chem. Ges., 1894)

(untitled) - Watson, J. D.; Crick, F. H. C. (Nature, 1953)

(untitled) - Yamaguchi, H.; Kobayashi, Y.; Kobayashi, R.; Takashima, Y.; Hashidzume, A.; Harada, A. (Nat. Commun., 2012)

(untitled) - Fleischmann, C.; Ritter, H. (Macromol. Rapid Commun., 2013)

(untitled) - Hu, P.; Tirelli, N. (Bioconjugate Chem., 2012)

(untitled) - Napoli, A.; Valentini, M.; Tirelli, N.; Müller, M.; Hubbell, J. A. (Nat. Mater., 2004)

(untitled) - Lallana, E.; Tirelli, N. (Macromol. Chem. Phys., 2013)

(untitled) - Li, M.-H.; Keller, P. (Soft Matter, 2009)

(untitled) - Carampin, P.; Lallana, E.; Laliturai, J.; Carroccio, S. C.; Puglisi, C.; Tirelli, N. (Macromol. Chem. Phys., 2012)

(untitled) - Napoli, A.; Boerakker, M. J.; Tirelli, N.; Nolte, R. J. M.; Sommerdijk, N. A. J. M.; Hubbell, J. A. (Langmuir, 2004)

(untitled) - Schmaljohann, D. (Adv. Drug Delivery Rev., 2006)

(untitled) - Liu, H. Y.; Zhu, X. X. (Polymer, 1999)

(untitled) - Dimitrov, I.; Trzebicka, B.; Müller, A. H. E.; Dworak, A.; Tsvetanov, C. B. (Prog. Polym. Sci., 2007)

(untitled) - Roy, D.; Brooks, W. L. A.; Sumerlin, B. S. (Chem. Soc. Rev., 2013)

(untitled) - de las Heras Alarcón, C.; Pennadam, S.; Alexander, C. (Chem. Soc. Rev., 2005)

(untitled) - Plummer, R.; Hill, D. J. T.; Whittaker, A. K. (Macromolecules, 2006)

(untitled) - Pietsch, C.; Schubert, U. S.; Hoogenboom, R. (Chem. Commun., 2011)

(untitled) - Jochum, F. D.; zur Borg, L.; Roth, P. J.; Theato, P. (Macromolecules, 2009)

(untitled) - Akiyama, H.; Tamaoki, N. (Macromolecules, 2007)

(untitled) - Narumi, A.; Fuchise, K.; Kakuchi, R.; Toda, A.; Satoh, T.; Kawaguchi, S.; Sugiyama, K.; Hirao, A.; Kakuchi, T. (Macromol. Rapid Commun., 2008)

(untitled) - Kujawa, P.; Segui, F.; Shaban, S.; Diab, C.; Okada, Y.; Tanaka, F.; Winnik, F. M. (Macromolecules, 2006)

(untitled) - Schmidt, B. V. K. J.; Hetzer, M.; Ritter, H.; Barner-Kowollik, C. (Macromol. Rapid Commun., 2013)

(untitled) - Winnik, F. M.; Davidson, A. R.; Hamer, G. K.; Kitano, H. (Macromolecules, 1992)

(untitled) - Kolb, H. C.; Finn, M. G.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2001)

(untitled) - Maatz, G.; Maciollek, A.; Ritter, H. (Beilstein J. Org. Chem., 2012)

(untitled) - Yu, B.; Chan, J. W.; Hoyle, C. E.; Lowe, A. B. (J. Polym. Sci., Part A: Polym. Chem., 2009)

(untitled) - Li, H.; Yu, B.; Matsushima, H.; Hoyle, C. E.; Lowe, A. B. (Macromolecules, 2009)

(untitled) - Xia, Y.; Burke, N. A. D.; Stöver, H. D. H. (Macromolecules, 2006)

(untitled) - Matyjaszewski, K.; Xia, J. (Chem. Rev., 2001)

(untitled) - Xia, Y.; Yin, X.; Burke, N. A. D.; Stöver, H. D. H. (Macromolecules, 2005)

(untitled) - Hales, M.; Barner-Kowollik, C.; Davis, T. P.; Stenzel, M. H. (Langmuir, 2004)

(untitled) - Freitag, R.; Baltes, T.; Eggert, M. (J. Polym. Sci., Part A: Polym. Chem., 1994)

(untitled) - Chung, J. E.; Yokoyama, M.; Aoyagi, T.; Sakurai, Y.; Okano, T. (J. Controlled Release, 1998)

(untitled) - Chung, J. E.; Yokoyama, M.; Suzuki, K.; Aoyagi, T.; Sakurai, Y.; Okano, T. (Colloids Surf., B, 1997)

(untitled) - Rekharsky, M. V.; Inoue, Y. (Chem. Rev., 1998)

(untitled) - Müller, B.-K.; Ritter, H. (J. Inclusion Phenom. Macrocyclic Chem., 2012)

(untitled) - Mayo, F. R. (J. Am. Chem. Soc., 1943)

Handbook of radical polymerization - Matyjaszewski, K.; Davis, T. P. (John Wiley and Sons, 2002)

(untitled) - Lessard, D. G.; Ousalem, M.; Zhu, X. X.; Eisenberg, A.; Carreau, P. J. (J. Polym. Sci., Part B: Polym. Phys., 2003)

(untitled) - Idziak, I.; Avoce, D.; Lessard, D.; Gravel, D.; Zhu, X. X. (Macromolecules, 1999)

(untitled) - Schild, H. G.; Tirrell, D. A. (J. Phys. Chem., 1990)

(untitled) - Duan, Q.; Miura, Y.; Narumi, A.; Shen, X.; Sato, S.-I.; Satoh, T.; Kakuchi, T. (J. Polym. Sci., Part A: Polym. Chem., 2006)

(untitled) - Kali, G.; Vavra, S.; László, K.; Iván, B. I. (Macromolecules, 2013)

(untitled) - Kemnitz, M.; Ritter, H. (Beilstein J. Org. Chem., 2012)

(untitled) - Ritter, H.; Sadowski, O.; Tepper, E. (Angew. Chem., Int. Ed., 2003)

(untitled) - André, X.; Zhang, M.; Müller, A. H. E. (Macromol. Rapid Commun., 2005)

(untitled) - Yan, J.; Ji, W.; Chen, E.; Li, Z.; Liang, D. (Macromolecules, 2008)